Method to observe Jupiter's radio emissions at high resolution using multiple LOFAR stations: a first case study of the Io-decametric emission using the Irish IE613, French FR606, and German DE604 stations. Issue 1 (14th October 2022) - Louis, Corentin K; Jackman, C M; Grießmeier, J-M; Wucknitz, O; McKenna, D J; Murphy, P C; Gallagher, P T; Carley, E P; Ó Fionnagáin, D; Golden, A; McCauley, J; Callanan, P; et al.
ABSTRACT: The Low Frequency Array (LOFAR) is an international radio telescope array, consisting of 38 stations in the Netherlands and 14 international stations spread over Europe. Here, we present an observation method to study the Jovian decametric radio emissions from several LOFAR stations (here Birr Castle in Ireland, Nançay in France, and Postdam in Germany), at high temporal and spectral resolution. This method is based on prediction tools, such as radio emission simulations and probability maps, and data processing. We report an observation of Io-induced decametric emission from 2021 June, and a first case study of the substructures that compose the macroscopic emissions (called millisecond bursts). The study of these bursts makes it possible to determine the electron populations at the origin of these emissions. We then present several possible future avenues for study based on these observations. The methodology and study perspectives described in this paper can be applied to new observations of Jovian radio emissions induced by Io, but also by Ganymede or Europa, or Jovian auroral radio emissions.